WeCanWork study: well-being of male cancer survivors working physically demanding jobs - Natalie V. Schwatka; Miranda Dally; Amy Dye-Robinson; Liliana Tenney; Carol E Brown; Madison Goering; Brian Williams; Lee S Newman; Cathy J Bradley (BMC Public Health)
Abstract Background Male cancer survivors performing physically demanding work have received less attention in the scientific literature compared to other groups. We hypothesized that men newly diagnosed with cancer have better well-being if they have less physically demanding jobs. Methods Seventy-six male workers completed the NIOSH Worker Well-being Questionnaire (WellBQ) approximately three months after starting cancer treatment. We used descriptive statistics to describe the demographics and worker well-being of the study sample and pooled t-tests to determine whether there were differences between respondents who had more physically demanding work and those with fewer physical demands. Results Male cancer survivors with physically demanding jobs reported poorer wage (p < 0.001)and benefit (p = 0.04) satisfaction, less autonomy (p = 0.03) and flexibility (p = 0.004), and greater financial insecurity (p = 0.002). They also experienced more negative job attitudes (p = 0.0003), and workplace safety concerns (p < 0.001) and less sleep (p = 0.05), with less support outside of work (p = 0.03) compared to men with less physically demanding jobs. Conclusions Our study highlights worker well-being differences approximately three months after initiating cancer treatment between men with and without physically demanding jobs. There are opportunities for employers to support worker well-being, specifically those with physically demanding jobs. Additionally, male cancer survivors with physically demanding jobs may need greater support outside of the workplace. Future research with a larger and longitudinal sample of male cancer survivors could inform how to support survivors from diagnosis through treatment and beyond.